How do African SMEs respond to climate risks? Evidence from Kenya and Senegal. (August 2018) - Crick, Florence; Eskander, Shaikh M.S.U.; Fankhauser, Sam; Diop, Mamadou
Highlights: Adaptive capacity determines the quality of current adaptation measures of SMEs. Supportive business environment encourages sustainable adaptation responses. Financial barriers lead SMEs to unsustainable adaptation practices. Current adaptation practices influence the planning for future climate change. Policy interventions can influence SMEs' ability to respond to climatic risks. Abstract: This paper investigates to what extent and how micro, small and medium-sized enterprises (SMEs) in developing countries are adapting to climate risks. We use a questionnaire survey to collect data from 325 SMEs in the semi-arid regions of Kenya and Senegal and analyze this information to estimate the quality of current adaptation measures, distinguishing between sustainable and unsustainable adaptation . We then study the link between these current adaptation practices and adaptation planning for future climate change. We find that financial barriers are a key reason why firms resort to unsustainable adaptation, while general business support, access to information technology and adaptation assistance encourages sustainable adaptation responses. Engaging in adaptation today also increases the likelihood that a firm is preparing for future climate change. The finding lends support to the strategy of many development agencies who use adaptation to current climate variability as a way of building resilience to future climate change. There is a clear role for public policy in facilitating good adaptation. The ability of firms to respond to climate risks depends in no small measure on factors such as business environment that can be shaped through policy intervention.